The Vegetation of Georgia (South Caucasus) - Nakhutsrishvili, George; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book describes richness and diversity of Georgia$1 (Bs vegetation. Contrasting ecosystems coexist on the relatively small territory of the country and include semi-deserts in East Georgia, Colchic forests with almost sub-tropical climate in West Georgia and subnival plant communities in high mountains. West Georgia lacks xerophilous vegetation zone and mesophilous forest vegetation spreads from the sea level to subalpine zone. The Colchic refugium (West Georgia) ensured survival of the Tertiary$1 (Bs mesophilous forest flora. Vertical profile of the vegetation is more complex in East Georgia with semi-desert, steppe and arid open forest zone. In South Georgia the montane zone represented by montane steppe is devoid of forestss
Environmental Conditions -- History of the Flora and Vegetation -- On the Altitudinal Differentiation of the Vegetation of Georgia -- On the Classification and Nomenclature of Plant Communities -- The Vegetation of Deserts, Steppes and Arid Open Woodlands -- Forest Vegetation of Georgia -- Near-Timberline Vegetation -- High-Mountain Vegetation -- The Hydrophytic Vegetation -- Synanthropic Vegetation -- Cultivated Flora -- Georgia: Protected Areas.
Keywords: Geography; Life sciences; Physical geography; Plant Ecology; Botany; Earth Sciences; Biogeosciences; Physical Geography; Plant Ecology; Plant Sciences